(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2026)
Brazilian psychologists are prohibited from acting in a way that modifies the sexual orientation or gender identity of their clients. However, such practices still exist, either through reparative therapies or corrective attitudes diluted in clinical practice. This study sought to evaluate the corrective attitudes and beliefs of clinical psychologists regarding sexual orientation and gender identity through an online questionnaire. The data indicated that 22.1% and 31.4% would be willing to modify the sexual orientation and gender identity, respectively, of their clients if requested. Corrective attitudes were not related to the respondents’ clinical approach. The professionals’ beliefs appeared as predictors in the logistic regressions of corrective attitudes and highlighted the presence of prejudice against bisexual people and pathologizing etiological beliefs. It is suggested, therefore, that affirmative action is fundamental for the safety of LGBTQ+ people in psychotherapeutic care.